Ecosystem Restoration through Managing Socio-Ecological Production Landscapes and Seascapes (SEPLS) - Nishi, Maiko; Subramanian, Suneetha M. (Satoyama Initiative Thematic Review, 2023)
This open access book is a compilation of case studies that provide useful knowledge and lessons that derive from on-the-ground activities and contribute to policy recommendations, focusing on the relevance of social-ecological production landscapes and seascapes (SEPLS) to ecosystem restoration. Building on the concept of SEPLS, the Satoyama Initiative promotes landscape approaches as integrative area-based strategies to bring together diverse stakeholders aiming to balance multiple objectives, including conservation and development, for the benefit of biodiversity and human well-being. Many of the SEPLS case studies from the International Partnership for the Satoyama Initiative (IPSI) offer rich evidence to help guide restoration efforts while advancing relevant knowledge and practices. The book highlights how the efforts in managing SEPLS can contribute to ecosystem restoration and sustainable development, looking at the strategies and approaches by which multiple stakeholders express, negotiate, and embrace their plural value perspectives of nature to restore ecosystems within a landscape or seascape. It begins with an introductory chapter followed by twelve case studies and a synthesis clarifying the relevance of the case study findings to policy and academic discussions. This book will be of interest to scholars, policymakers and professionals in the field related to sustainable development, especially on SDGs 15 and 17.